KIAA1429 and ALKBH5 Oppositely Influence Aortic Dissection Progression via Regulating the Maturation of Pri-miR-143-3p in an m6A-Dependent Manner - Wang, Peng; Wang, Zhiwei; Zhang, Min; Wu, Qi; Shi, Feng; Yuan, Shun (Frontiers in Cell and Developmental Biology, 2021)
Despite decades of study into aortic dissection (AD), a lethal cardiovascular emergency due to a tear in the aorta intima or bleeding within the aortic wall, leading to the separation of the different layers of it, the factors that influence its progression and the deeper regulatory mechanisms remain poorly understood. Nowadays, with the maturity of N6-methyladenosine (m6A) sequence technology, m6A modification, one type of RNA epigenesis, has gradually become a new research hotspot for epigenetic molecular regulation. Especially recently, increasing evidence has revealed that m6A modification functions as a pivotal post-transcriptional modification to influence the progression of multiple diseases. Based on these findings, it is reasonable to speculate that m6A modification may affect the onset and progression of AD. To explore the validity of our conjecture and to elucidate its underlying molecular mechanism of action, we conducted the present study. In this study, we found that KIAA1429 is downregulated while ALKBH5 is upregulated in aortic tissues from AD patients. Furthermore, gain- and loss-of-function studies showed that KIAA1429 and ALKBH5 can oppositely regulate HASMC proliferation, HAEC apoptosis, and AD progression in AngII-infused mice. Mechanistically, we demonstrated that KIAA1429/ALKBH5-mediated m6A modifications can regulate the processing of pri-miR-143-3p through interacting with the microprocessor protein DGCR8, thus indirectly regulating the downstream target gene of mature miR-143-3p, DDX6, to perform their biological functions in vitro and in vivo. Our findings have revealed a novel connection between m6A modification and AD progression and may provide a novel molecular basis for subsequent researchers to search for novel therapeutic approaches to improve the health of patients struggling with AD.